Svenska kattägares inställning till vaccination - Arnersten, Elin (SLU/Dept. of Animal Environment and Health (until 231231), 2012)
Background: Vaccination is an important part in cats’ welfare. It both helps to prevent the individual cat from catching a disease or lessen the symptoms of it, and protects the entire cat population from an epidemic. It is the cat owner who makes the decision to vaccinate or not. Understanding the cat owners’ perspective regarding vaccination may improve communication between the owner and the veterinary nurse, which may lead to a higher vaccination rate among cats.